The Importance of Darmaga IV SDN Students' Awareness in Increasing Interest in Reading - Imas Nurhidayati Aisyah; Endah Robiah Adawiyah; Badru Sohim (Indonesian Journal of Educational Science and Technology, 2022)
Interest in reading is a person's strong desire to read and analyze and understand the contents of what he reads. Therefore there are several factors that cause students' low interest in reading. Based on this, the problem in this study is how interest in reading and the factors that cause interest in reading in class VI SDN DARMAGA IV. The purpose of this study was to determine students' interest in reading in class VI at SDN DARMAGA IV. The research method used is descriptive qualitative method. The results showed that students' interest in reading was good with less interest in reading. Based on the results of the analysis of the data obtained, there are two factors that cause students' lack of interest in reading, namely internal factors, which are factors originating from students, namely the ability to read, understand the meaning contained in the reading, lack of habit of reading, reading books on the orders of the teacher, students rarely look for books or reading materials as needed. While external factors are those caused by a school environment that is not supportive, a reading culture that is lacking in the school environment, literacy programs that have not run optimally, school madding that has never been updated, the role of the school library that has not been maximized.